Magazine Journalism - Tim Holmes; Nice, Liz (London Sage, 2012)
At a time when magazines are undergoing active redefinition, this book represents a welcome intervention. It engages with a host of pressing issues in a manner alert to professional priorities while, at the same time, encouraging new ways of thinking about the challenges shaping this fast-moving field. Holmes and Nice are trustworthy guides, taking the reader on what proves to be a fascinating journey."
Keywords: Media